Challenge Demcare: management of challenging behaviour in dementia at home and in care homes – development, evaluation and implementation of an online individualised intervention for care homes; and a cohort study of specialist community mental health care for families - Esme Moniz-Cook (Programme Grants for Applied Research, 2017)
Background: Dementia with challenging behaviour (CB) causes significant distress for caregivers and the person with dementia. It is associated with breakdown of care at home and disruption in care homes. Challenge Demcare aimed to assist care home staff and mental health practitioners who support families at home to respond effectively to CB. Objectives: To study the management of CB in care homes (ResCare) and in family care (FamCare). Following a conceptual overview, two systematic reviews and scrutiny of clinical guidelines, we (1) developed and tested a computerised intervention; (2) conducted a cluster randomised trial (CRT) of the intervention for dementia with CB in care homes; (3) conducted a process evaluation of implementation of the intervention; and (4) conducted a longitudinal observational cohort study of the management of people with dementia with CB living at home, and their carers. Review methods: Cochrane review of randomised controlled trials; systematic meta-ethnographic review of quantitative and qualitative studies. Design: ResCare – survey, CRT, process evaluation and stakeholder consultations. FamCare – survey, longitudinal cohort study, participatory development design process and stakeholder consultations. Comparative examination of baseline levels of CB in the ResCare trial and the FamCare study participants. Settings: ResCare – 63 care homes in Yorkshire. FamCare – 33 community mental health teams for older people (CMHTsOP) in seven NHS organisations across England. Participants: ResCare – 2386 residents and 861 staff screened for eligibility; 555 residents with dementia and CB; 277 ‘other’ residents; 632 care staff; and 92 staff champions. FamCare – every new referral (n = 5360) reviewed for eligibility; 157 patients with dementia and CB, with their carer; and 26 mental health practitioners. Stakeholder consultations – initial workshops with 83 practitioners and managers from participating organisations; and 70 additional stakeholders using eight group discussions and nine individual interviews. Intervention: An online application for case-specific action plans to reduce CB in dementia, consisting of e-learning and bespoke decision support care home and family care e-tools. Main outcome measures: ResCare – survey with the Challenging Behaviour Scale; measurement of CB with the Neuropsychiatric Inventory (NPI) and medications taken from prescriptions; implementation with thematic views from participants and stakeholders. FamCare – case identification from all referrals to CMHTsOP; measurement of CB with the Revised Memory and Behaviour Problems Checklist and NPI; medications taken from prescriptions; and thematic views from stakeholders. Costs of care calculated for both settings. Comparison of the ResCare trial and FamCare study participants used the NPI, Clinical Dementia Rating and prescribed medications. Results: ResCare – training with group discussion and decision support for individualised interventions did not change practice enough to have an impact on CB in dementia. Worksite e-learning opportunities were not readily taken up by care home staff. Smaller homes with a less hierarchical management appear more ready than others to engage in innovation. FamCare – home-dwelling people with dementia and CB are referred to specialist NHS services, but treatment over 6 months, averaging nine contacts per family, had no overall impact on CB. Over 60% of people with CB had mild dementia. Families bear the majority of the care costs of dementia with CB. A care gap in the delivery of post-diagnostic help for families supporting relatives with dementia and significant CB at home has emerged. Higher levels of CB were recorded in family settings; and prescribing practices were suboptimal in both care home and family settings. Limitations: Functionality of the software was unreliable, resulting in delays. This compromised the feasibility studies and undermined delivery of the intervention in care homes. A planned FamCare CRT could not proceed because of insufficient referrals. Conclusions: A Cochrane review of individualised functional analysis-based interventions suggests that these show promise, although delivery requires a trained dementia care workforce. Like many staff training interventions, our interactive e-learning course was well received by staff when delivered in groups with facilitated discussion. Our e-learning and decision support e-tool intervention in care homes, in its current form, without ongoing review of implementation of recommended action plans, is not effective at reducing CB when compared with usual care. This may also be true for staff training in general. A shift in priorities from early diagnosis to early recognition of dementia with clinically significant CB could bridge the emerging gap and inequities of care to families. Formalised service improvements in the NHS, to co-ordinate such interventions, may stimulate better opportunities for practice models and pathways. Separate services for care homes and family care may enhance the efficiency of delivery and the quality of research on implementation into routine care. Future work: There is scope for extending functional analysis-based interventions with communication and interaction training for carers. Our clinical workbooks, video material of real-life episodes of CB and process evaluation tool resources require further testing. There is an urgent need for evaluation of interventions for home-dwelling people with dementia with clinically significant CB, delivered by trained dementia practitioners. Realist evaluation designs may illuminate how the intervention might work, and for whom, within varying service contexts. Trial registration: Current Controlled Trials ISRCTN02553381 (the ResCare trial) and ISRCTN58876649 (the FamCare study). Funding: This project was funded by the National Institute for Health Research (NIHR) Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 5, No. 15. See the NIHR Journals Library website for further project information.